2021
DOI: 10.3390/cancers13040714
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Radiotherapy with Vaccination and Immune Checkpoint Inhibition Differently Affect Primary and Abscopal Tumor Growth and the Tumor Microenvironment

Abstract: Radiotherapy (RT) is known to have immune-modulatory properties. We hypothesized that RT and inactivated whole tumor cell vaccines generated with high hydrostatic pressure (HHP) synergize to retard the tumor growth which can be additionally improved with anti-PD-1 treatment. In abscopal tumor models, we injected mice with B16-F10 melanoma or TS/A mammary tumors. To evaluate the efficiency of RT in combination with HHP vaccines, we locally irradiated only one tumor with 2 × 8 Gy or 3 × 8 Gy. HHP vaccines furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 67 publications
2
24
0
1
Order By: Relevance
“…In the above dual tumor model used by Ruckert et al, the addition of anti-PD1 to radiation therapy improved primary and distant tumor control, but distant tumor control was still not impacted by tumor-specific vaccination (204). Notably, the immunomodulatory effects of radiation including upregulation regulatory molecules such as PDL1 were restricted to the tumor in the radiation field, and did not impact the out of field tumor (204). Therefore, the out of field tumor remained resistant, despite in field success.…”
Section: Radioimmunogenicitymentioning
confidence: 96%
See 1 more Smart Citation
“…In the above dual tumor model used by Ruckert et al, the addition of anti-PD1 to radiation therapy improved primary and distant tumor control, but distant tumor control was still not impacted by tumor-specific vaccination (204). Notably, the immunomodulatory effects of radiation including upregulation regulatory molecules such as PDL1 were restricted to the tumor in the radiation field, and did not impact the out of field tumor (204). Therefore, the out of field tumor remained resistant, despite in field success.…”
Section: Radioimmunogenicitymentioning
confidence: 96%
“…If our therapies can impact the distant tumor, they must be responsive to immune therapies that rely purely on increased tumor-specific T cell numbers. A recent example of this can be seen in Ruckert et al, where using a dual flank tumor model, they demonstrated that systemic vaccination against tumor specific antigens only impacted the growth of the irradiated tumor (204). Although the distant tumor was injected a few days following primary tumor injection and therefore had an improved tumor environment, it remained resistant to increased circulating tumor-specific T cells (204).…”
Section: Radioimmunogenicitymentioning
confidence: 99%
“…However, a large number of patients do not respond properly to immune therapies targeting such ICMs. Therefore, improving existing immunotherapies with optimized RT schemes and identifying other RT-regulated ICMs besides PD-L1 is an important step to increase response rates to radio-immunotherapies [52,53].…”
Section: A Dose Of 5x30gy Mainly Increases the Expression Of Immune Suppressive Icms Independently Of The Hpv Statusmentioning
confidence: 99%
“…For example, vac-cination is an emerging field of research that has brought promising results for the future of immunotherapy. It is feasible to boost RT-induced immune responses and to achieve immunosuppression by inhibiting immunosuppressive molecules, such as PD-1, with activated whole tumor cell vaccines [47]. Additionally, recent studies have reported that elevated levels of novel oxidative phosphorylation (OXPHOS) in tumors are an important factor associated with immunotherapy efficacy [48,49].…”
Section: Using Radiotherapy To Overcome Immunotherapy Resistance: Updates and Challengesmentioning
confidence: 99%